Significados da morte e do morrer para a equipe multiprofissional de uma unidade de terapia intensiva adulto - Barbosa, Alessandra Monteiro Guimarães Carvalho (2013)
Death is an event that, to be respected, no need to cover the historical dimensions and socio-cultural context and personal experiences, which can affect the individual and group behavior. With social changes in the process of dying, death moved to within healthcare institutions, causing health professionals who work in intensive care units coexist daily with death and dying. It is important to know the meanings that caregivers attach to death and dying, as well as the factors affecting this interaction, for discussions and reflections both in work practice, as in academic life, to assist the health care team the best live with the phenomenon studied. This research aimed to: identify and describe the meanings that members of the multidisciplinary team of Adult Intensive Care Unit of a University Hospital have about the process of dying and death and analyze the factors affecting the coexistence of these health professionals Adult Intensive Care Unit with death and dying. A descriptive qualitative study, using the technique of semi-structured interviews with a sample of 21 health professionals that Unit was conducted. For data analysis, we used the method of thematic content analysis. Trying to identify the meanings given by health professionals to death and dying, fell into two categories: non-scientific view of death and dying and scientific view of death and dying, and found the following meanings about death: a natural process, a step to fulfill a physiological event and the total extinction of human beings. This variability is explained in the definitions of addiction knowledge and personal experience to elaborate a concept of death. Analyzing the factors that interfere with the interaction of health professionals with death and the dying process the following categories were found: Temporality of death; Ways of coping; Technologies that prolong life; and Education. The results point to a better acceptance of death when it occurs with the elderly; failure points in academic education with regard to discussing the subject of death and dying; spirituality and detachment, being used as a way of coping; technology and prolonging the process of dying. The deployment of aid groups to professional, proposed by the interviewees as a space for expression of feelings arising from work as well as work on personal and professional experiences, and the process of dying and death in its different looks (physiological, ethical, social , psychological and spiritual), may be the triggering of improving the quality of personal and professional lives of these workers.